2022
DOI: 10.1177/15588661221125201
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Participation in Recreational Activities on Students’ Resilience and Sense of Belonging

Abstract: The purpose of this study was to examine the effects of participation in five different recreational activities—instructor-led group fitness or exercise classes, intramural sports, open recreation, outdoor adventure activities and/or trips, or sport clubs—on undergraduates’ resilience and sense of belonging. We used data from the Multi-Institutional Study of Leadership (MSL) survey, which was completed by 48,232 undergraduates at 71 U.S. colleges and universities in spring 2018. We used propensity score matchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The study also highlighted gender differences in self-efficacy and expectations of results, emphasizing the importance of creating a strong atmosphere of physical exercise and sports culture to improve students' physical health [6] . Soria et al (2022) aimed to examine the effects of participation in five different recreational activities on undergraduates' resilience and sense of belonging. Ordinary least squares analyses suggested that participation in various recreational activities had positive effects on students' resilience and sense of belonging [7] .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also highlighted gender differences in self-efficacy and expectations of results, emphasizing the importance of creating a strong atmosphere of physical exercise and sports culture to improve students' physical health [6] . Soria et al (2022) aimed to examine the effects of participation in five different recreational activities on undergraduates' resilience and sense of belonging. Ordinary least squares analyses suggested that participation in various recreational activities had positive effects on students' resilience and sense of belonging [7] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Soria et al (2022) aimed to examine the effects of participation in five different recreational activities on undergraduates' resilience and sense of belonging. Ordinary least squares analyses suggested that participation in various recreational activities had positive effects on students' resilience and sense of belonging [7] . Liu et al (2023) explored potential categories of college students' sports behavior motivation and the differences between different family social classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modern campus facilities have been designed to provide more than just access to fitness equipment and recreation areas; they are increasingly becoming a destination for fitness, health, wellness, academics, and social connection (Bogar, 2008;Wilson et al, 2020). This investment in campus recreation has well-documented benefits that extend beyond health and fitness to student retention, academic performance, stress reduction, social connections and community, and self-confidence (Das et al, 2021;Forrester, 2015;Litwiller et al, 2021;Makubuya et al, 2020;Milton et al, 2020;Sanderson et al, 2018;Soria et al, 2022;Zegre et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes empirically associated with sport club participation include healthy body composition (Chu & Zhang, 2018), fitness benefits (Lower et al, 2013), leadership development (Haines & Fortman, 2008), practical competence (Flosdorf et al, 2016), resilience (Soria et al, 2022), friendship (Czekanski et al, 2023), and academic performance (Lifschutz, 2019). However, there is little indication of whether these findings reflect targeted outcomes sport club programs are intentionally trying to achieve.…”
mentioning
confidence: 99%